Making the Complicated Simple: A Minimizing Carrier Strategy on Innovative Nanopesticides - Shangguan, Wenjie; Huang, Qiliang; Chen, Huiping; Zheng, Yingying; Zhao, Pengyue; Cao, Chong; Yu, Manli; Cao, Yongsong; Cao, Lidong (Nano-Micro Letters, 2024)
The flourishing progress in nanotechnology offers boundless opportunities for agriculture, particularly in the realm of nanopesticides research and development. However, concerns have been raised regarding the human and environmental safety issues stemming from the unrestrained use of non-therapeutic nanomaterials in nanopesticides. It is also important to consider whether the current development strategy of nanopesticides based on nanocarriers can strike a balance between investment and return, and if the complex material composition genuinely improves the efficiency, safety, and circularity of nanopesticides. Herein, we introduced the concept of nanopesticides with minimizing carriers (NMC) prepared through prodrug design and molecular self-assembly emerging as practical tools to address the current limitations, and compared it with nanopesticides employing non-therapeutic nanomaterials as carriers (NNC). We further summarized the current development strategy of NMC and examined potential challenges in its preparation, performance, and production. Overall, we asserted that the development of NMC systems can serve as the innovative driving force catalyzing a green and efficient revolution in nanopesticides, offering a way out of the current predicament. Highlights: 1 Nanopesticides with minimizing carrier were prepared through prodrug molecular design and molecular self-assembly. 2 Nanopesticides with minimizing carrier are expected to solve the environmental risks caused by the unrestricted introduction of nanomaterials. 3 Future development and challenges of nanopesticides with minimizing carrier.